Periscoping economics through someone else's eyes: A real world (Twitter) app. (September 2016) - Dowell, Chelsea T.; Duncan, Daniel F.
Abstract: Students and instructors alike are constantly seeking out real world examples of economic concepts. Current college students use their phone as extensions of themselves. While many students and instructors utilize Twitter, Periscope – an application (app) owned by Twitter – has not yet been capitalized on in the economics classroom. Periscope allows Twitter members to live stream video footage of their current location and to have text conversations between members. Periscope creates a unique opportunity for students to see life in other countries in real time while communicating with individuals abroad. We present an assignment that incorporates the use of Periscope as a means of analyzing and forecasting GDP and standard of living for countries across the globe.